ALTERNATIVE NON-HYDROMETALLURGICAL ROUTES FOR ELECTRIC ARC FURNACE DUST (EAFD) TREATMENT: A CRITICAL REVIEW (REMUNOM, 2025)
Electric arc furnace dust (EAFD) is a hazardous by-product from steel production in electric arc furnaces, characterized by a complex chemical composition and high concentrations of heavy metals such as zinc, lead, and iron. This review aims to critically evaluate the main non-hydrometallurgical treatment routes applied to EAFD, focusing on pyrometallurgical processes, thermal and physical treatments, and immobilization strategies such as stabilization/solidification (S/S). Illustrative flowcharts, comparative tables, and technical, environmental, and economic performance assessments are provided for each approach. The study also highlights emerging applications of EAFD in the construction materials industry, including its use in cement and sintered ceramics. Research gaps and future perspectives are discussed in light of industrial feasibility and environmental sustainability. This review offers a comprehensive overview of technological alternatives for the recovery or safe disposal of EAFD, prioritizing solutions aligned with the circular economy